The Effect of Chronic Administration of Lathyrogen (Beta-Aminopropionitrile) on Blood Clotting and Fibrinolytic System in Rabbits - Bańkowski, E; Worowski, K (Thrombosis and Haemostasis, 1969)
The effect of chronic intoxication of rabbits with beta-aminopropionitrile on blood clotting and fibrinolysis was studied.The increase of clotting time of whole blood and recalcified plasma accompanied with the decrease of factor IX, XI and XIII level were observed. On the other hand the significant increase of fibrinogen content and soluble complexes of fibrin monomers level was found.A deep inhibition of fibrinolytic activity of plasma was stated. The decrease of thromboplastic and fibrinolytic activity of saline extracts of some internal organs was also observed. The mechanism of above described changes and their significance in pathology are discussed.